Treating status epilepticus in clinical practice—a multi-national survey in Germany, Austria, and Switzerland - Möller, Leona; Fisch, Urs; Habermehl, Lena; Jünemann, Clara (Frontiers in Neurology, 2025)
BackgroundStatus epilepticus (SE) is a life-threatening neurological emergency, and exhibits significant variability in clinical management despite established guidelines. This study evaluates current practices across German speaking countries.MethodsA web-based survey (December 2023–May 2024) assessed SE treatment strategies among 83 neurologists and neurointensivists from Germany, Austria, and Switzerland. Cases were presented to analyze diagnostic and therapeutic preferences.ResultsThe preferred benzodiazepine for first line treatment was lorazepam, chosen by 71.6% of the respondents. In the case of established SE, 35.4% chose levetiracetam as the preferred ASM. Propofol in combination with sufentanil/fentanyl was the preferred anesthetic of choice in 65.4% of respondents. For super-refractory status epilepticus (SRSE), 41.5% prefer to add further ASM, with valproic acid (67.1%), and lacosamide (64.5%) being the most frequently selected. Only 31.8% reported that their emergency services have a standard operating procedure (SOP) for SE treatment, and the choice of the preferred benzodiazepine varied in the preclinical setting, with midazolam being the most commonly used. 1) First-line therapy: Lorazepam (71.6% in-hospital), midazolam (50% prehospital), 2) Second-line therapy: Levetiracetam (35.4%) and lacosamide (13.4%) were the most common choices, 3) Refractory SE: Propofol with opioids (65.4%) were preferred for anesthesia, 4) Prehospital care: 31.8% of emergency services lacked standardized protocols; midazolam dosing varied widely (2–10 mg).DiagnosticsLaboratory testing was universal (96.9%), but MR-imaging (10%) and clinical use of prognostic scores (6.2%) were underutilized.ConclusionThis survey highlights the variability in clinical practice for managing status epilepticus in German-speaking countries. Persistent heterogeneity in SE management underscores the need for standardized protocols, particularly in prehospital care and refractory SE therapy.